The Malay-Muslim Insurgency in Southern Thailand--Understanding the Conflict's Evolving Dynamic RAND Counterinsurgency Study--Paper 5 - Chalk, Peter (RAND Corporation, 2008)
Current unrest in the Malay-Muslim provinces of southern Thailand hascaptured growing national, regional, and international attention due to theheightened tempo and scale of rebel attacks, the increasingly jihadistundertone that has come to characterize insurgent actions, and the centralgovernment's often brutal handling of the situation on the ground. Thispaper assesses the current situation and its probable direction.